Association of inflammation cytokines with cognitive function in first-episode major depressive disorder - Xi, Yan Qing; Wang, Zong Qi; Li, Guo Juan; Hao, Zhuo Qun; Nie, Jia Hui; Li, Jin Xiang; Tan, Yu Ting; Hu, Xiao Dong; Wang, Gen Wei; Liu, Sha; Wang, Yan Fang (Frontiers in Psychiatry, 2025)
ObjectiveAbnormal cognitive functioning is a core symptom of Major Depressive Disorder (MDD) and is strongly correlated with MDD prognosis. Current studies suggest that the occurrence of MDD may be related to oxidative stress-induced inflammation, hypothalamic-pituitary-adrenal axis disorders, diminished monoamine function and microbe-brain-gut axis, among other pathways. In recent years, the relationship between the immune-inflammatory response and MDD has been a hot topic of research, but how the relationship between immunoinflammation and cognitive function is manifested in MDD is still unclear. In this study, we examined cognitive function characteristics, serum inflammatory factors, brain-derived neurotrophic factor, and their correlations before and after pharmacological treatment(paroxetine hydrochloride tablets) in patients with first-episode major depressive disorder, aiming to identify objective biomarkers for cognitive function assessment.MethodsWe included 22 patients with first-episode major depressive disorder and 27 healthy volunteers from the community during the same period. The Hamilton Depression Scale-17 (HAMD-17) assessed the severity of depressive symptoms at baseline and after 8 weeks of treatment. The Repeatable Battery for the Assessment of Neuropsychological Status(RBANS) evaluated cognitive function, and serum samples were collected to determine levels of inflammatory and neurotrophic factors at these two time points. For healthy volunteers, only HAMD-17 scale scores, RBANS scale scores, and serum samples were taken at baseline. Spearman’s correlation analyzed the relationship between inflammatory factors, neurotrophic factors, and cognitive function. Multiple linear regression determined factors affecting cognitive function in first-time patients.ResultsBaseline findings indicated that patients’ IL-6 and TNF-α levels exceeded those of healthy individuals, while their IFN-α levels were below; their scores in language, attention, delayed memory, and the RBANS scale were also lower than healthy counterparts. Post-treatment, patients’ BDNF, IL-6, and TNF-α levels remained higher than those of healthy subjects, and their IFN-α levels were still lower; their language and attention scores were also inferior. Association analyses revealed an association between BDNF and visuospatial/constructional ability scores and language scores in patients with MDD at baseline, and a positive relationship between TNF-α and attention score. Multiple regression analysis indicated an association between TNF-α levels and attention scores in MDD patients at baseline.ConclusionsOur study concludes that TNF-α and BDNF correlate with cognitive function in MDD at baseline, and furthermore, TNF-α could potentially serve as an objective biomarker to support the assessment of attentional function at baseline.